Too Many Cooks Spoil the Broth: How High-Status Individuals Decrease Group Effectiveness - Groysberg, Boris; Polzer, Jeffrey T.; Elfenbein, Hillary Anger (Organization Science, 2011)
Can groups become effective simply by assembling high-status individual performers? Though an affirmative answer may seem straightforward on the surface, this answer becomes more complicated when group members benefit from collaborating on interdependent tasks. Examining Wall Street sell-side equity research analysts who work in an industry in which individuals strive for status, we find that groups benefited—up to a point—from having high-status members, controlling for individual performance. With higher proportions of individual stars, however, the marginal benefit decreased before the slope of this curvilinear pattern became negative. This curvilinear pattern was especially strong when stars were concentrated in a small number of sectors, likely reflecting suboptimal integration among analysts with similar areas of expertise. Control variables ensured that these effects were not the spurious result of individual performance, department size or specialization, or firm prestige. We discuss the theoretical implications of these results for the literatures on status and groups, along with practical implications for strategic human resource management.